Physio training as important part of education of young tennis players - Waldzinska, E. (Archives of Budo Science of Martial Arts and Extreme Sports, 2023)
Background & Study Aim: Developmental trends in tennis require coaches to engage in comprehensive work with players from the early stages of training. It is important to note that in a long-term training program for young athletes, in addition to teaching technique and tactics, attention should be given to the motor development of the players. Furthermore, in order to ensure the holistic development of young athletes and injury prevention, it is essential to incorporate medical training based on exercises that improve joint stability, kinesthesia, and neuromuscular coordination into the sports training process. The aim of the research is the broaden knowledge of physio training in the of young tennis players.